Draft Sixth Five Year Plan 1980-85 Vol I Approach and GN. Statements Government of Tripura - Planning Commission (Planning Commission, 1980)
With an area of 10,477 Sq. KM, Tripura has a large population of 20.65 lakhs in 1980 most of whom are displaced persons. The projected estimate of population for the year 1985 is 24.05 lakhs. The density of population which 149 per Sq. KM. in 1971 is expected to increase to 230 in 1985. 60% of the area of the State consists of hills where plough cultivation is not possible.
Government of Tripura